Pemecahan Masalah Numerasi Siswa Pemecahan Masalah Numerasi Siswa di daerah 3T dalam Rangka Penyelenggaraan Pendidikan inklusif di SD : Pemecahan Masalah Numerasi Siswa di daerah 3T dalam Rangka Penyelenggaraan Pendidikan inklusif di SD - Herman Alimuddin; Andi Yunarni Yusri; Ruri Muhammad PD; Muh. Rahmat (Mandalika Mathematics and Educations Journal, 2025)
This study aims to provide an in-depth overview of the numeracy problem-solving skills of elementary school students in 3T (frontier, outermost, and disadvantaged) regions, particularly in Pangkep Regency, within the framework of inclusive education. The selection of research subjects was based on the results of the Minimum Competency Assessment (AKM), focusing on numeracy, which includes mastery of basic mathematical concepts and their application in real-life situations. Data collection was carried out through numeracy tests and in-depth interviews. The findings reveal that all respondents, both from grade IV and grade V, were categorized as having low numeracy skills. In the number pattern question, only 16% of grade IV students and 35% of grade V students answered correctly. For the number name question, the achievement rate was 58% for grade IV and 25% for grade V. Meanwhile, in the data analysis question, none of the grade IV students answered correctly, and only 30% of grade V students provided the correct answer. These results indicate that students’ numeracy literacy is low, particularly in reading, understanding, and analyzing information. Contributing factors include the lack of practice with context-based problems, limited learning facilities, the continued use of conventional teaching methods, and the socio-economic background of families. Based on these conditions, there is a need for numeracy learning interventions that are contextual, problem-based, and supported by teacher training to improve the numeracy skills of students in 3T areas. The novelty of this research lies in its specific combination of three aspects: problem-solving, numeracy skills, and inclusive education, particularly in 3T regions.